Difference modeling for design space exploration and comparison of three-dimensional structural simulation results. (October 2019) - Thelin, Christopher; Bunnell, Spencer; Salmon, John; Gorrell, Steve
Design space exploration is an important part of design in engineering fields. Recent research employs surrogate models to emulate finite element analyses across a design space, allowing rapid design space exploration. With interactive speeds, there exists a need for tools that help designers compare designs to one another. This difference model is comprised of a three-dimensional rendering of the geometry with the location and magnitude of differences between the two designs displayed as colors on the model surface. This visualization is combined with juxtaposed views of the objects being compared. A user experiment was conducted with 28 volunteers to demonstrate whether or not including the difference model in the visualization can improve speed and accuracy for various comparative design tasks. It was found that, for certain comparison tasks, there is indeed statistical evidence that using the difference model alongside the two juxtaposed views improved speed and accuracy when making design judgments between two different designs.